Engineered Asymmetric Composite Membranes with Rectifying Properties. Issue 4 (2nd December 2015) - Wen, Liping; Xiao, Kai; Sainath, Annadanam V. Sesha; Komura, Motonori; Kong, Xiang‐Yu; Xie, Ganhua; Zhang, Zhen; Tian, Ye; Iyoda, Tomokazu; Jiang, Lei
Abstract : Asymmetric composite membranes with rectifying properties are developed by grafting pH‐stimulus‐responsive materials onto the top layer of the composite structure, which is prepared by two novel block copolymers using a phase‐separation technique. This engineered asymmetric composite membrane shows potential applications in sensors, filtration, and nanofluidic devices.